Masscommight 2023 highlighting communication and media / Efina Hamdan, Nur Alyani Mohd Shukri and Siti Nur Fadzilah Abdullah - Hamdan, Efina; Mohd Shukri, Nur Alyani; Abdullah, Siti Nur Fadzilah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Rembau, 30 November 2023 - Final semester students of the Diploma in Communication and Media (MC110) from Universiti Teknologi MARA (UiTM) Negeri Sembilan Branch, Rembau Campus organised the MasscomMight 2023 programme on 29 and 30 November 2023. The programme was held at Dewan Biduanda UiTM Rembau Campus, starting from 8am to 6pm. The main purpose of organizing this programme was to provide exposure to school students and higher education institutions around Rembau and Alor Gajah about communication and media. MasscomMight 2023 programme consisted of five talk sessions with various industry representatives, such as Mr. Zaki Zainal from Astro Arena who shared about public speaking, representatives from Mask Team, Mr. Mohd Ridzuani and Ms. Nurul Syahirah, who discussed on advertising. Additionally, Ms. Norazreen from MaryKay shared about professional grooming and there was a writing workshop titled “Air Liur Emas” conducted by Ms. Nurul Nisha and the director of “Air Liur Emas” himself, Mr. Jef Haziman. Mr. Syafil Syazwan, an alumnus of UiTM, provided insights into journalism.